Lactic Acid Fermentation of Pomegranate Juice as a Tool to Improve Antioxidant Activity - Pontonio, E.; Montemurro, M.; Pinto, D.; Marzani, B.; Trani, A.; Ferrara, G.; Mazzeo, A.; Gobbetti, M.; Rizzello, C. G. (Frontiers in Microbiology, 2019)
An increasing consumer demand for pomegranate has been globally observed, mainly thanks to the scientific evidence related to its functional and health-promoting features. Pomegranate fruits from twenty accessions identified in Southeastern Italy were characterized according to morphological and chemical features. Juices extracted from pomegranate fruits were fermented with selected Lactobacillus plantarum PU1 and the antioxidant activity investigated. Whey was added to juices to promote the microbial growth. Fermentation led to the increase of the radical scavenging activity (up to 40%) and significant inhibition of the linoleic acid peroxidation. The three fermented juices showing the highest antioxidant activity, and the corresponding unfermented controls, were further characterized. In detail, the cytotoxicity and the protective role towards artificially induced oxidative stress were determined on murine fibroblasts Balb 3T3 through the determination of the viability and the intracellular ROS (reactive oxygen species) scavenging activity (RSA). RSA reached values of ca. 70% in fermented juices, being ca. 40% higher than the unfermented and control samples. Phenols compounds of the pomegranate juices obtained from accessions “Bitonto Piscina”, “Sanrà nero” and “Wonderful (reference cultivar) were analyzed through ultrahigh pressure liquid chromatography coupled with mass spectrometry, showing that a marked increase (up to 60%) of the ellagitannins derivatives occurred during fermentation. Sensory analysis showed suitability of the fermented juices to be used as beverage and food ingredient.